Application of a Two-Analyte Integrated Population Pharmacokinetic Model to Evaluate the Impact of Intrinsic and Extrinsic Factors on the Pharmacokinetics of Polatuzumab Vedotin in Patients with Non-Hodgkin Lymphoma - Dan Lu; Tong Lu; Rong Shi; Leonid Gibiansky; Priya Agarwal; Colby S. Shemesh; Randall C. Dere; Uzor Ogbu; Jamie Hirata; Pascal Chanu; Sandhya Girish; Jin Yan Jin; et al. (Pharmaceutical Research, 2020)
Purpose The established two-analyte integrated population pharmacokinetic model was applied to assess the impact of intrinsic/extrinsic factors on the pharmacokinetics (PK) of polatuzumab vedotin (pola) in patients with non-Hodgkin lymphoma (NHL) following bodyweight-based dosing. Methods Model simulations based on individual empirical Bayes estimates were used to evaluate the impact of intrinsic/extrinsic factors as patient subgroups on Cycle 6 exposures. Intrinsic factors included bodyweight, age, sex, hepatic and renal functions. Extrinsic factors included rituximab/obinutuzumab or bendamustine combination with pola and manufacturing process. The predicted impact on exposures along with the established exposure-response relationships were used to assess clinical relevance. Results No clinically meaningful differences in Cycle 6 pola exposures were found for the following subgroups: bodyweight 100–146 kg versus 38–<100 kg, age ≥ 65 years versus <65 years, female versus male, mild hepatic impairment versus normal, mild-to-moderate renal impairment versus normal. Co-administration of rituximab/obinutuzumab or bendamustine, and change in the pola manufacturing process, also had no meaningful impact on PK. Conclusions In patients with NHL, bodyweight-based dosing is adequate, and no further dose adjustment is recommended for the heavier subgroup (100–146 kg). In addition, no dose adjustments are recommended for other subgroups based on intrinsic/extrinsic factors evaluated.

High-frequency compensation for seismic data based on adaptive generalized S transform - Hui-Feng Li; Jin Wang; Zheng-Rong Wei; Fei-Long Yang (Applied Geophysics, 2020)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Decrypting the crosstalk of noncoding RNAs in the progression of IPF - Yujuan Wang; Han Xiao; Fenglian Zhao; Han Li; Rong Gao; Bingdi Yan; Jin Ren; Junling Yang (Molecular Biology Reports, 2020)
Idiopathic pulmonary fibrosis (IPF) is an agnogenic, rare, and lethal disease, with high mortality and poor prognosis and a median survival time as short as 3 to 5 years after diagnosis. No effective therapeutic drugs are still not available not only in clinical practice, but also in preclinical phases. To better and deeper understand pulmonary fibrosis will provide more effective strategies for therapy. Mounting evidence suggests that noncoding RNAs (ncRNAs) and their interactions may contribute to lung fibrosis; however, the mechanisms underlying their roles are largely unknown. In this review, we systematically summarized the recent advances regarding the crucial roles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) and crosstalk among them in the development of IPF. The perspective for related genes was well highlighted. In summary, ncRNA and their interactions play a key regulatory part in the progression of IPF and are bound to provide us with new diagnostic and therapeutic targets.

Effects of topography on dynamic responses of single piles under vertical cyclic loading - Li-ming Qu; Xuan-ming Ding; Chong-rong Wu; Yong-hong Long; Jin-chuan Yang (Journal of Mountain Science, 2020)

Cell bioreactor culture of Orostachys cartilaginous A. Bor. and involvement of nitric oxide in methyl jasmonate-induced flavonoid synthesis - Yue-Jun Hao; Xi-Hua Cui; Jin-Rong Li; Xiao-Li An; Hao-Ding Sun; Xuan-Chun Piao; Mei-Lan Lian (Acta Physiologiae Plantarum, 2020)